2017
DOI: 10.4317/jced.54471
|View full text |Cite
|
Sign up to set email alerts
|

Sealing effectiveness of fissure sealant bonded with universal adhesive systems on saliva-contaminated and noncontaminated enamel

Abstract: BackgroundThe effectiveness of sealants is dependent upon their adhesion to enamel surface. The aim of the study was to evaluate the sealing ability of a pit and fissure sealant used with a universal adhesive (etch-and-rinse vs. self-etch modes) when the site is contaminated with saliva. Adhesive properties were evaluated as microleakage and scanning electron microscopic (SEM) characteristics.Material and MethodsA total of 72 mandibular third molars were randomly divided into 6 groups (n=12). Occlusal pits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…21 Thus, it is possible that applying a bonding agent prior to a sealant on carious surfaces enhanced the retention rate, which occurred on saliva-contaminated surfaces. [12][13][14][15] This is because the volatility of the ethanol-based bonding agent provides deep flow into the micro-spaces of the etched enamel and effectively displaces the trapped water in the moist enamel. 17,22 In this study, none of the participants in the complete retention group had changes in their ICDAS score.…”
Section: Discussionmentioning
confidence: 99%
“…21 Thus, it is possible that applying a bonding agent prior to a sealant on carious surfaces enhanced the retention rate, which occurred on saliva-contaminated surfaces. [12][13][14][15] This is because the volatility of the ethanol-based bonding agent provides deep flow into the micro-spaces of the etched enamel and effectively displaces the trapped water in the moist enamel. 17,22 In this study, none of the participants in the complete retention group had changes in their ICDAS score.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when saliva was introduced during the application of the material, microleakage significantly increased, and 1-second air-thinning of the saliva, 10-second air-drying of the saliva, or reconditioning before sealant application did not significantly decrease the microleakage. Memarpour et al [16] also have evaluated the effect of saliva contamination on sealing properties of fissure sealant bonded with universal adhesive systems. They revealed that saliva contamination after etching the tooth had an adverse effect on the adhesion of the sealant to the treated enamel.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of microleakage after saliva contamination, which observed in these two studies, is similar to the results of the present study. However, the effect of the time of contamination during light curing was not considered in the Peng et al 15 and Memarpour et al [16] studies. Basir et al [17] carried out a study on the effect of the different adhesive system on fissure sealant microleakage with or without saliva contamination.…”
Section: Discussionmentioning
confidence: 99%
“…The universal bond was used as its monomers composition differs from other adhesive systems. The selfetching option allows good chemical and micromechanical bonding to the enamel surface and it can alternate the conventional etching (31,32). Moreover, Universal adhesives are simpler, more user-friendly, and less technique-sensitive, and reduce patient chair time.…”
mentioning
confidence: 99%
“…Moreover, Universal adhesives are simpler, more user-friendly, and less technique-sensitive, and reduce patient chair time. These privileges are advantageous in pediatric dentistry (32).…”
mentioning
confidence: 99%